Nitrogen Nanobubbles on Viola cornuta growth and its effect on post-harvest quality - Rosalinda, S.; Pusponegoro, Annisa; Alam, Hilman Syaeful; Destiana, Irna Dwi; Nurjanah, Sarifah; Widyasanti, Asri; Fawaiz, Husni Syamil (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Viola cornuta is an edible flower known for its high antioxidant content and aesthetic appearance. Advanced technologies, such as nanobubbles, combined with optimized cultivation methods, can greatly improve floral quality. Nanobubbles, gas bubbles with a diameter of < 200 nm, can increase dissolved gas levels in liquids. This study aimed to analyze the application of nitrogen nanobubbles on Viola cornuta growth and its effect on post-harvest quality. The experiment was carried out where the plants were cultivated in pots with a Nutrient Film Technique (NFT) irrigation system without a gully cover. Nitrogen nanobubbles were dissolved in nutrient solution every 30 minutes in the morning, delivered at a flow rate of 1 liter per minute through a swirling-flow nozzle. The results revealed that the application of nanobubbles during cultivation did not significantly affect most growth parameters, except for fresh weight and color (CIE Lch). However, nanobubbles significantly enhanced post-harvest quality parameters, with the exception of shelf life. Furthermore, nitrogen nanobubbles demonstrated a positive effect flower number, root length, and flower antioxidant activity. This study suggests that nitrogen nanobubles hold potential for improving the quality of Viola cornuta. Future research is recommended to explore the use of drip irrigation system with the same medium as in this study or NFT without a soil medium.